1999
DOI: 10.1152/jappl.1999.87.5.1923
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the corticospinal control of ventilation by changes in reflex respiratory drive

Abstract: We have determined whether changes in PCO(2) above and below eucapnia modulate the precision of the voluntary control of breathing. Twelve trained subjects performed a compensatory tracking task in which they had to maintain the position of a cursor (perturbed by a variable triangular forcing function) on a fixed target by breathing in and out of a spirometer (ventilatory tracking; at 10 l/min). Before each task, subjects hyperventilated for 5 min, and the end-tidal PCO(2) (PET(CO(2))) was controlled; tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Our estimation of the combined chemoreflex contribution to resting ventilation differs from that estimated by Corfield et al (1999). They estimated the contribution by calculating the error of a ventilatory tracking task during hypocapnia, eucapnia and hypercapnia.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…Our estimation of the combined chemoreflex contribution to resting ventilation differs from that estimated by Corfield et al (1999). They estimated the contribution by calculating the error of a ventilatory tracking task during hypocapnia, eucapnia and hypercapnia.…”
Section: Figurementioning
confidence: 95%
“…However, Corfield et al (1999) have recently suggested that the contribution of the combined central and peripheral chemoreflexes to resting breathing may be inconsequential.…”
mentioning
confidence: 99%
“…These activities include activities relating to airway clearance (cough, sneezing) or to the need for food ingestion without aspiration (Bartlett and Leiter, 2012). They also include breathing behaviours depending on cortical networks that allow voluntary apnoea (McKay et al, 2008) and the execution of voluntary respiratory manoeuvres that can be complex and very precise (Colebatch et al, 1991;Corfield et al, 1999;Gandevia and Rothwell, 1987;Plotkin et al, 2010;Similowski et al, 1996). In humans, speech represents the most frequent disruption of automatic breathing by a voluntary activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, even with most levels of anesthesia (e.g., supra minimum alveolar concentration [MAC] concentrations of inhalational anesthetics), painful surgical stimuli that do not elicit a purposeful movement will elicit a change in ventilation. The role of chemoreflexes in determining resting ventilation in awake subjects is subject to some controversy [6,7] and it may be that a "wakefulness drive", as proposed by Fink [8], plays a major part, possibly accounting for the often irregular breathing that is observed at rest.…”
Section: Introductionmentioning
confidence: 99%